(untitled) (Palíndromo, 2013)
This article aims to take a few steps through the discontinuous, uncertain and winding contemporary landscapes, where the virtual and the real interpenetrate, different perspectives intersect and multiple discourses touch each other. A conversation happens between an art teacher and a mirror, thinking of art education as a means of creating other becomings, other sensitivities, new ways of living, of being “in group” and of a poetic potentializing of the process of learning. Before the crisis we find ourselves as inventors of worlds and builders of the inheritance which we inevitably leave to those who are born after us, the artistic act can create estrangements, generate discontinuities and oblique views, question the habitual ways of perception and, as those who live every moment, every time, like the first time, inaugurate a new time, producing differences, freedoms and possibilities of meeting.